DROPOUTS RATES IN RELIGIOUS EDUCATION IN MUZARABANI DISTRICT SECONDARY SCHOOLS IN MASHONALAND CENTRAL PROVINCE OF ZIMBABWE - KASOWE, RITTAH (IJRDO- Journal of Educational Research, 2017)
This present study’s aim was to examine the causes of dropouts of secondary school pupils in Religious Education in Muzarabani District. A random sample of 75 teachers was used. The descriptive survey design was used. The questionnaire was the sole instrument used to gather data. The study revealed that lack of resources, culture conflicts, pupils’ attitudes, methodological problems among other factors, contributed significantly towards high dropout rates in the subject. The study recommends that teachers should use the eclectic, multi-faith approaches when teaching Religious education. The study also recommends that the school and the home should play complementary roles in order to reduce cases of students dropping out of the subject.